The Feasibility of a Modified Exclusive Endoscopic Transcanal Transpromontorial Approach for Vestibular Schwannomas - Moon, In Seok; Cha, Dongchul; Nam, Sung-Il; Lee, Hyun-Jin; Choi, Jae Young (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective We evaluated the feasibility of an exclusive endoscopic transcanal transpromontorial approach (EETTA) for the treatment of small vestibular schwannomas (VSs) limited to the internal auditory canal (IAC), and introduced a modification without external auditory canal closure.Methods Between June 2016 and June 2017, seven patients with VS underwent surgery using a modified EETTA. Treatment outcomes, including efficacy of tumor resection, preservation of function, operation time, and quality of life (QOL), were evaluated.Results The patients preoperatively exhibited Koos Grade I/II tumors and severe-to-profound hearing loss. Gross total resection was accomplished in all cases. There were no major complications, and all patients exhibited normal facial nerve function immediately after surgery. The mean follow-up period was 12.9 months. The operation time (average 196.3 ± 64.9 minutes) and hospitalization period (average 7.4 ± 1.0 days) were favorable. Short Form-36 scores for QOL showed unremarkable results compared with previous reports.Conclusions The modified EETTA was effective in the removal of VSs in the IAC. It can be an alternative surgical option for small VSs.
Keywords: endoscopy; ear canal; cochlea; acoustic neuroma